Relationship between oral health literacy and oral health-related quality of life in patients with bladder cancer - Fatemeh Babadi; Ahmad Ahmadi; Mohsen Sarkarian; Maria Cheraghi (Frontiers Media S.A., 2024)
IntroductionBladder cancer is one of the most important diseases that threatens oral and dental health due to its nature and side effects of chemotherapy. Therefore, the present study was conducted to investigate the relationship between oral health literacy and oral health-related quality of life in patients with bladder cancer.MethodsThis cross-sectional study was conducted on patients with bladder cancer in Ahvaz, 2023. Subjects were selected randomly from the patients those were registered in Cancer Registry Center in Ahvaz Jundishapur University of Medical sciences and invited to Golestan Hospital for data collection through clinical evaluation, the Oral Health Literacy Adult Questionnaire (OHL-AQ), and the Oral Health Impact Profile-14 (OHIP-14PER) questionnaire. The data were analyzed using Pearson correlation coefficient, independent t-test, and analysis of variance.ResultsThe number of participants was 194. The mean oral health literacy in patients with bladder cancer was 9.74 ± 2.39, indicating insufficient oral health literacy. A significant association was observed between OHL-AQ and DMFT index, but no significant association was found between OHIP-14PER and DMFT index. Furthermore, a significant correlation was found between OHL-AQ and OHIP-14PER (r = −0.68) in patients with bladder cancer.ConclusionBased on the findings of the present study, all dimensions of oral health literacy have correlation with the oral health-related quality of life in patients with bladder cancer. Therefore, adopting oral health behaviors and increasing oral health literacy can be the best way to improve the oral health-related quality of life to among patients with bladder cancer.